2012
DOI: 10.1063/1.4767060
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics study of the equation of state and the structure of supercooled aqueous solutions of methanol

Abstract: We perform molecular dynamics computer simulations in order to study the equation of state and the structure of supercooled aqueous solutions of methanol at methanol mole fractions x(m) = 0.05 and x(m) = 0.10. We model the solvent using the TIP4P/2005 potential and the methanol using the OPLS-AA force field. We find that for x(m) = 0.05 the behavior of the equation of state, studied in the P - T and P - ρ planes, is consistent with the presence of a liquid-liquid phase transition, reminiscent of that previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 97 publications
(142 reference statements)
3
17
0
Order By: Relevance
“…The LLCP is still found to exist for low concentrations. 392 A FTS dynamical crossover was also measured in methanol solutions at low concentrations, 393 within this framework the FTS dynamical crossover should mark the crossing of the Widom line.…”
Section: Thermodynamics and Dynamics Of Aqueous Solutionsmentioning
confidence: 97%
“…The LLCP is still found to exist for low concentrations. 392 A FTS dynamical crossover was also measured in methanol solutions at low concentrations, 393 within this framework the FTS dynamical crossover should mark the crossing of the Widom line.…”
Section: Thermodynamics and Dynamics Of Aqueous Solutionsmentioning
confidence: 97%
“…There are several theoretical and computational studies of the phase behavior of supercooled aqueous solutions. [54][55][56][57][58][59][60][61][62] Paschek calculated the excess chemical potential of Ar in TIP5P-E water using the particle insertion method and found that the solubility of Ar in LDL is much higher than that in HDL. 62 Le and Molinero performed MD simulations of an aqueous solution of hydrophilic particles using a coarse-grained model.…”
Section: Introductionmentioning
confidence: 99%
“…Corradini et al calculated the isotherms of pressure using MD simulations for several solution systems. [54][55][56][57] They showed that the liquid-liquid critical point shifts to lower pressures and higher temperatures as the concentration of NaCl increases. 54,55 The liquid-liquid coexistence conditions of pure water is represented by a line in the pressuretemperature plane, whereas the coexistence conditions of an aqueous solution should be a twodimensional region in the plane for a value of composition.…”
Section: Introductionmentioning
confidence: 99%
“…[57][58][59] Also solutions can represent a viable route to study the supercooled region of water. 21,[60][61][62][63][64][65] The existence of a FSC in concentrated solutions of methanol and of LiCl has been recently found [66][67][68] with ultrafast femtosecond optical Kerr effect (OKE) spectroscopy, nuclear magnetic resonance (NMR) diffusion measurements, Fourier-transform infrared (FTIR) measurements, and temperature-dependent rheology although different techniques, namely, broadband dielectric and light scattering spectroscopy in a broad frequency range experiments on water and LiCl(aq) do not find it. 69 The difference among the probes must, however, be considered while analyzing different kinds of relaxation times.…”
Section: Introductionmentioning
confidence: 99%